The attitude of the Transcarpathian population toward religion and the perception of religious tourism - Tóth, Attila; Sass, Enikő; Olah, Natalia (Human Geography Journal, 2025)
The article examines the religiosity of the Transcarpathian population and its attitudes toward religious tourism as a promising direction for regional tourism development. The historical multi-confessional and multi-ethnic character of Transcarpathia has shaped a rich sacral landscape, including unique Rusyn wooden churches, medieval temples, and pilgrimage sites, which together form a substantial basis for religious tourism. The empirical foundation of the study is a questionnaire survey conducted among 515 residents, allowing the authors to assess levels of religiosity, participation in religious trips, awareness of sacral heritage, and readiness to engage in organized religious tours.The findings show that over 96% of respondents consider themselves religious, with more than half regularly attending church services and participating in pilgrimages. However, public awareness of key sacral attractions remains low. The study identifies infrastructural limitations and insufficient promotion of religious tourism resources as the main barriers to further development. At the same time, the strong local interest in religious travel, combined with the unique cultural heritage and the growing global demand for non-mass, authentic tourist experiences, indicates significant prospects for the post-war development of religious tourism in the region.